Analisis Laporan Keuangan PT Adira Dinamika Multi Finance Tbk Berdasarkan Rasio Profitabilitas dan Rasio Solvabilitas (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This research aims to assess the financial performance of PT Adira Dinamika Multi Finance Tbk over the period from 2022 to 2024 by utilizing financial ratio analysis, particularly related to profitability and solvability. The approach used is quantitative descriptive, using secondary data obtained from the company's annual financial reports. The results of this study indicate that the company's profitability performance has varied, peaking in 2023 and declining in 2024, although it remains within a healthy category. Conversely, the company's funding structure shows a tendency to rely more on debt, as evidenced by the increased solvability ratio over the last three years. Nevertheless, the company's overall financial condition remains stable and aligns with the characteristics of the financing sector.